1996
DOI: 10.1029/95wr03637
|View full text |Cite
|
Sign up to set email alerts
|

Scale Dependence of Soil Permeability to Air: Measurement Method and Field Investigation

Abstract: This work investigates the dependence of soil permeability to air on sampling scale in near‐surface unsaturated soils. A new dual‐probe dynamic pressure technique was developed to measure permeability in situ over different length scales and different spatial orientations in the soil. Soils at three sites were studied using the new technique. Each soil was found to have higher horizontal than vertical permeability. Significant scale dependence of permeability was also observed at each site. Permeability increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Pneumatic tests were conducted at multiple soil gas probes using a vacuum pump (November 2009, September 2010, and November 2010). The soil‐air permeability was estimated from the measured flow rate and pressure using the spherical flow model described in Garbesi et al (). Snow density was measured on core samples (March 2010, January 2011, and March 2011).…”
Section: Field Methodsmentioning
confidence: 99%
“…Pneumatic tests were conducted at multiple soil gas probes using a vacuum pump (November 2009, September 2010, and November 2010). The soil‐air permeability was estimated from the measured flow rate and pressure using the spherical flow model described in Garbesi et al (). Snow density was measured on core samples (March 2010, January 2011, and March 2011).…”
Section: Field Methodsmentioning
confidence: 99%
“…Transport properties upscaling has been investigated by simulating flow through numerically generated random porous media, assuming a specific (usually lognormal) permeability distribution [e.g., Gelhar and Axness , 1983; Ababou et al , 1989]. Concurrently, efforts have been expended to estimate the scaling properties and the distribution of permeability in geomaterials and geologic formations [e.g., Brace , 1980; Goggin et al , 1992; Garbesi et al , 1996; Painter , 1996; Schulze‐Makuch et al , 1999]. Recent laboratory studies [ Henriette et al , 1989; Tidwell and Wilson , 1997, 1999a, 1999b, 2000] attempted to quantify the spatial fluctuations of permeability in meter‐scale blocks as a function of measurement volume (see also Zhang et al [2000] who examined centimeter‐scale samples).…”
Section: Introductionmentioning
confidence: 99%
“…Sisson and Wierenga (1981) showed that 5‐, 25‐, and 127‐cm‐diameter rings gave similar mean infiltration rates, although the mean increased from 6.25 to 8.48 and 8.51 cm d −1 Davis et al (1999) compared constant‐head well permeameter, 6‐ by 7‐cm cores, and 20‐ by 30‐cm cores, and found that the largest core size gave estimates from one to three orders of magnitude greater than the other two methods. Air permeability measurements have been similarly shown to be scale dependent, with estimates increasing as much as a factor of 20 when the scale of measurement increased from 0.1 to 2 m (e.g., Garbesi et al, 1996; Tidwell and Wilson, 1999).…”
mentioning
confidence: 99%